vBerlinV2N: Recreating a Cellular Network Measurement Campaign With Simulations - Christian L. Vielhaus; Mauri Seidel; Vincent Latzko; Alexander Grob; Peter Sossalla; Martin Reisslein; Frank H. P. Fitzek (IEEE Access)
System-level simulations play a crucial role in evaluating the behaviors of cellular networks, yet most studies rely on synthetic simulation scenarios rather than reproducing realistic network deployments. This paper presents vBerlinV2N, a system-level simulation model based on the network simulator 3 (ns-3) that replicates the BerlinV2N measurement campaign conducted in a real-live Long Term Evolution (LTE) network. We describe the methodology for setting up and calibrating the simulation to match real-world observations, including network topology, radio conditions, and user mobility. We discuss the challenges of accurately recreating real deployments in simulations by identifying missing information in the public domain and limitations of ns-3. Furthermore, we generate a simulation dataset with vBerlinV2N that closely resembles the BerlinV2N measurement dataset. A statistical evaluation of the measured and simulated datasets validates that the simulated vBerlinV2N dataset captures the essential statistical patterns of the measured BerlinV2N dataset. We analyze the distributions as well as the temporal and spatial variations of the received signal quality metrics of the radio environments and compare the end-to-end throughput, delay, and handovers.